Change in cognition before and after non‐central nervous system cancer diagnosis: A population‐based cohort study. Issue 10 (27th May 2021) - van der Willik, Kimberly D.; Jóźwiak, Katarzyna; Hauptmann, Michael; van de Velde, Edolie E.D.; Compter, Annette; Ruiter, Rikje; Stricker, Bruno H.; Ikram, M. Arfan; Schagen, Sanne B.
Abstract: Objective: Clinical studies showing that non‐central nervous system cancer patients can develop cognitive impairment have primarily focused on patients with specific cancer types and intensive treatments. To better understand the course of cognitive function in the general population of cancer patients, we assessed cognitive trajectories of patients before and after cancer diagnosis in a population‐based setting. Methods: Between 1989 and 2014, 2211 participants from the population‐based Rotterdam study had been diagnosed with cancer of whom 718 (32.5%) had undergone ≥1 cognitive assessment before and after diagnosis. Cognition was measured every 3 to 6 years using a neuropsychological battery. Linear mixed models were used to compare cognitive trajectories of patients before and after diagnosis with those of age‐matched cancer‐free controls (1:3). Results: Median age at cancer diagnosis was 70.3 years and 47.1% were women. Most patients (68.1%) had received local treatment only. Cognitive trajectories of patients before and after cancer diagnosis were largely similar to those of controls. After diagnosis, the largest difference was found on a memory test (patients declined with 0.14 units per year on the Word Learning Test: delayed recall [95% CI = −0.35; 0.07] and controls with 0.09 units [95% CI = −0.18;‐0.00], p for difference = .59). Conclusions: In this longitudinal cohort, cancer did not appear to alter the trajectory of change in cognitive test results over time from that seen in similar individuals without cancer, although most cancer patients did not receive systemic therapies. Future studies should focus on identifying subgroups of patients who are at high risk for developing cognitive impairment.